Salud laboral en Brasil y regulación y control de la toxicidad relacionada con el benceno - Silva Graciani, Fernanda [UNESP]; Vidrih Ferreira, Gabriel Luis Bonora (My University, 2014)
The Brazilian normative system recognizes, indirectly, the possibility of exceptional situations where the workers are exposed to circumstances which adversely affect their health. However, taking into account the special characteristics of some substances, its suitability to the traditional technical of definition of a tolerance limit for purposes of additional paying is not possible; so there is a need for continued progress. This is the case of benzene, whose occupational regulation in recent times had a significant transformation, adding new dimensions to the protection in the workplace in Brazil, setting the TRV (Technological Reference Value) as a new form of control as its exposure. Thus, the aim of this work is to analyze the way how the protection to occupational health in Brazil is accomplished, focusing on the regulation and forms of control of toxicity related to the presence of benzene in the workplace, especially the use of TRV as referral mechanism to find the most favorable condition to the worker. In order to support this study, techniques of documental research and literature were used, with analysis of legal provisions, besides the technical and scientific papers about the forms of control and regulation for the presence of harmful agents in the workplace, as well as compared to the toxicological aspects related to occupational exposure to benzene.
Occupational health in Brazil and regulation and control of benzene toxicity
Keywords: Benzene; Legislation; Occupational health; Toxicology